Oxidative Stability at Different Storage Conditions and Adulteration Detection of Prickly Pear Seeds Oil - Fatima Ettalibi; Abderraouf El Antari; Chemseddoha Gadhi; Hasnaâ Harrak (Journal of Food Quality)
Lipid oxidation and adulteration have a negative impact on functionality and notoriety of foods especially vegetable oils and cause economic losses. The present study investigates the control of two commercial quality aspects of prickly pear seeds oil (PPSO): oxidative stability during storage and detection of adulteration. Peroxide index, specific extinction coefficients K232 and K270, free acidity, and fatty acids composition were evaluated during different periods of incubation (6, 12, and 18 months) at various temperatures (4°C, 25°C, 40°C, and uncontrolled room temperature ranging between 4°C and 40°C) with different packaging (protected and unprotected from sunlight, with and without nitrogen gas bubbling). Based on the physicochemical and biochemical parameters evolution, this study has shown that PPSO stored at 4°C for 18 months preserves the initial quality. However, at 40°C, an intense lipid oxidative process occurred after 6 months of storage. The changes have also affected fatty acids composition, especially rates of linoleic and oleic acids. The shelf-life of oils stored at 25°C and at uncontrolled room temperature can be limited to 6 months. Regarding the impact of light and nitrogen bubbling, sunlight has affected seriously the oxidative stability of oils after 12 months of storage and the bubbling with nitrogen has improved their stability when they have been stored in clear glass bottles. The levels of adulteration detection using fatty acids as markers are relatively high. The detection of oil adulteration can be depicted by fatty acids composition up to 15% of olive and almond oils and up to 20% of rapeseed oil. The iodine value could also be an indicator of the sunflower oil presence in PPSO. Therefore, other minor compounds including sterols and tocopherols should be investigated to depict PPSO adulteration with cheaper oils and to determine lower levels of detection in order to ensure the authenticity of PPSO.